2022
DOI: 10.3389/fmars.2022.1040466
|View full text |Cite
|
Sign up to set email alerts
|

Starvation shrinks the mussel foot secretory glands and impairs the byssal attachment

Abstract: Mussel is an economically and ecologically important species widely distributed throughout the world. The mussel adheres to the attachment substrate by secreting byssus external to the body. Various environmental and biological factors influence the process of byssus secretion, and the present study investigated the effect of starvation on byssal secretion in the hard-shelled mussel Mytilus coruscus. Histological changes in mussel foot secretory glands and gene expression of mussel foot proteins were also dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…disease, marine heatwaves). Previous research has shown that under starvation stress, insufficient energy intake may negatively affect protein synthesis in mussels, leading to thinner byssal threads and reduced breaking force—these directly increase the risk of mussels detaching from the attachment substrate (Zheng et al 2022 ). One to 2 weeks starvation of Perna canaliculus also results in a 15–40% reduction of their carbohydrate stores, which is thought to make them more susceptible to stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…disease, marine heatwaves). Previous research has shown that under starvation stress, insufficient energy intake may negatively affect protein synthesis in mussels, leading to thinner byssal threads and reduced breaking force—these directly increase the risk of mussels detaching from the attachment substrate (Zheng et al 2022 ). One to 2 weeks starvation of Perna canaliculus also results in a 15–40% reduction of their carbohydrate stores, which is thought to make them more susceptible to stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%